Desymmetric esterification catalysed by bifunctional chiral N-heterocyclic carbenes provides access to inherently chiral calix[4]arenes - Vojtěch Dočekal; Ladislav Lóška; Adam Kurčina; Ivana Císařová; Jan Veselý (Nature Communications)
Abstract Calix[4]arenes display inherent chirality, with broad applications in synthetic and medicinal chemistry and in materials sciences. However, their use is hindered by their limited synthetic accessibility, primarily due to the lack of enantioselective methods for preparing chiral calix[4]arenes with an ABCC substitution pattern. Here, we address this challenge by presenting a simple, efficient, and metal-free protocol for organocatalytic desymmetrisation of prochiral diformylcalix[4]arenes. Through this highly effective and sustainable approach, we synthesize structurally unique products in gram-scale reactions. Accordingly, this method facilitates extensive post-functionalisations of the carbonyl groups, including for organocatalyst development. Furthermore, our experimental mechanistic studies demonstrate that desymmetrisation determines enantiocontrol in esterification reactions catalysed by N-heterocyclic carbenes. These findings underscore the broad potential of this method for providing versatile access to inherently chiral calix[4]arenes with an ABCC substitution pattern while offering a valuable platform for asymmetric molecular recognition and catalysis.